Pembelajaran Pada Masa Pandemi Covid-19 - Luh Devi Herliandry; Nurhasanah Nurhasanah; Maria Enjelina Suban; Heru Kuswanto (JTP - Jurnal Teknologi Pendidikan, 2020)
The Pandemic COVID-19 has changed various aspects of human life today, especially in education. This requires all elements of education to adapt and continue the rest of the semester. The purpose of this study as a general review of learning during the COVID-19 pandemic. This research uses descriptive content analysis study method. The analysis was carried out on international, national articles and similar sources related to learning solutions during the pandemic. Online learning is an effective solution for activating classrooms even though schools have closed because time and place are at risk during this pandemic. However, this learning technique is important to be evaluated according to local conditions given the distribution of facilities and the ability of parents to provide different online learning facilities to students in Indonesia.